x+8(x-7)=-2(3x+1)+6x

Simple and best practice solution for x+8(x-7)=-2(3x+1)+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+8(x-7)=-2(3x+1)+6x equation:


Simplifying
x + 8(x + -7) = -2(3x + 1) + 6x

Reorder the terms:
x + 8(-7 + x) = -2(3x + 1) + 6x
x + (-7 * 8 + x * 8) = -2(3x + 1) + 6x
x + (-56 + 8x) = -2(3x + 1) + 6x

Reorder the terms:
-56 + x + 8x = -2(3x + 1) + 6x

Combine like terms: x + 8x = 9x
-56 + 9x = -2(3x + 1) + 6x

Reorder the terms:
-56 + 9x = -2(1 + 3x) + 6x
-56 + 9x = (1 * -2 + 3x * -2) + 6x
-56 + 9x = (-2 + -6x) + 6x

Combine like terms: -6x + 6x = 0
-56 + 9x = -2 + 0
-56 + 9x = -2

Solving
-56 + 9x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + 9x = -2 + 56

Combine like terms: -56 + 56 = 0
0 + 9x = -2 + 56
9x = -2 + 56

Combine like terms: -2 + 56 = 54
9x = 54

Divide each side by '9'.
x = 6

Simplifying
x = 6

See similar equations:

| x^4-25x^2+135=0 | | 48x-32+28=78 | | 7z-0.3=8z | | j-21=21 | | -w+13=5w-5 | | 2w+56=176 | | 1.25x+5=-3 | | 24x=27x-6 | | -3.7y-5.7=-0.8y+3 | | 3(x+1)-2x=x+3 | | 2y+40=100 | | -4x+-9=-5-6x | | 10x+4=4x+7 | | 3(2m-4)=2m+4m-4 | | .75a+.75a+a=15 | | 9v-8(1+6v)= | | 24+2y+13=20+4y-19 | | 4(n+1)+3=-35-2n | | 3(2+r)-2r=2r+11 | | 8y-16=5y+2 | | 7(t-5)+8t=5(3t+5)-13 | | 13*k=52 | | 2x-5y+z=5 | | 5(k-2)-2(k+4)=6 | | 7+5x=-33 | | 10u-6=2(5u-3) | | y-19=-3y-12 | | 2x+52=90 | | w+3/5+4=6 | | 2y+5=-14 | | -6(p+8)=-6p+12 | | -4(y-1)+-3=25 |

Equations solver categories